Evaluasi Permukiman Kumuh Berbasis Water Sensitive Urban Design (WSUD) - Asmaul Husna; Ihsan Ihsan; Wiwik Wahidah Osman (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2019)
The development of settlements in urban areas is inseparable from the rapid rate of growth of urban population. Maradekaya Kelurahan is one of 143 urban villages in Makassar City which is part of the slum area with a moderate category. (SK Slum Mayor of Makassar City, 2015). Water Sensitive Urban Design is a land planning concept and engineering approach that integrates urban water cycles, including rainwater, groundwater and wastewater and clean water management into urban designs to minimize environmental damage and increase aesthetic and recreational appeal. This concept is considered capable of being one of the solutions in handling slums in Maradekaya Kelurahan by utilizing appropriate measures against existing components. The purpose of this study is to identify opportunities for the application of the concept of Water Sensitive Urban Design in the study area and produce concept directions as an evaluation of slums. The method used is descriptive qualitative and quantitative methods of existing WSUD components in Maradekaya Kelurahan. Based on the results of the study, found a variety of conditions varying from the two components of the Water Sensitive Urban Design starting from the conditions, extent, characteristics, potential, problems and availability of a variety of each component, this is used as an introduction to the analysis based on the characteristics of the components owned, policies and guidelines used the researcher. This research resulted in the direction of the concept of applying Water Sensitive Urban Design based on two components in Maradekaya Village to reduce the growth of slums in Makassar City.